Maxillary protraction in adult cleft lip and palate by a rigid external distraction device with dentoskeletal anchorage - Akarsu, Bengisu; Taner, Tulin; Tuncbilek, Gokhan; Mavili, M. Emin (European Journal of Dentistry, 2012)
Objective: The objective is to evaluate the effects of maxillary distraction osteogenesis (DO) in an adult patient with unilateral cleft lip and palate (UCLP) by using a rigid external distraction (RED) device with dentoskeletal anchorage.Method: 31-year-old male patient with UCLP with severe maxillary hypoplasia, dolichofacial growth pattern, negative overjet and 1.5 mm openbite. After pre-surgical orthodontic treatment, an intra-oral appliance was modified to prevent extrusion of the molars and clockwise rotation of the mandible. Stainless steel plates were soldered bilaterally to the intra oral appliance at the level of canines. During surgery, miniplates were inserted in the maxillary segment and fixed to the plates of the intra oral appliance with screws.Results: The mean distraction length was 12 mm immediately after DO. SNA increased from 73o to 82o after distraction. A significant advancement of the maxilla and correction of the sagittal Class III skeletal relationship was achieved. The vertical position of the mandible and the face was kept stable, and the soft tissue profile became more balanced.Conclusion: This intra oral appliance design achieved desired skeletal changes during maxillary protraction with RED device in dolichofacial CLP patient. Occlusion and facial profile changes was found to be stable in 1-year follow-up. (Eur J Dent 2012;6:206-211)
Keywords: Orthodontics; cleft lip; external distraction